Learning in Work A Negotiation Model of Socio-personal Learning - Smith, Raymond (Professional and Practice-based Learning,, 2018)
This book explores and progresses the concept of negotiation as a means of describing and explaining individuals' learning in work. It challenges the undertheorised and generic use of the concept in contemporary work-learning research where the concept of negotiation is most often deployed as a taken for granted synonym for interaction, co-participation and collaboration and, hence, used to unproblematically account for workers' learning as engagement in social activity. Through a focus on workers' personal practice and based on extensive longitudinal empirical research, the book advances a conceptual framework, The Three Dimensions of Negotiation, to propose a more rigorous and work-learning specific understanding of the concept of negotiation. This framework enables workers' personal work practices and their contributions to the personal, organisational and occupational changes that evidence learning to be viewed as negotiations enacted and managed, within contexts that are in turn sets of premediate and concurrent negotiations that frame the transformations on and from which on-going negotiations of learning and practice ensue. The book does not seek to supplant understandings of the rich and valuable concept of negotiation. Rather, it seeks to develop and promote a more explicit use of the concept as a socio-personal learning concept at the same time as it opens alternative perspectives on its deployment as a metaphor for individual's learning in work. .